Permainan Lilin Plastisin Sebagai Stimulasi Motorik Halus Anak dalam Persiapan Menulis - Indri Nuareni; Sepia Nuriska; Sheila Fitrunnisa (Indonesian Journal of Society Engagement, 2022)
This study aims to find out how giving stimulation using plasticine wax games has an effect on children's fine motor development in preparation for writing. The method used is by filling out a questionnaire using a Google form which is disseminated online. The results of the fine motor research analysis through filling out the questionnaire obtained 35 respondents, namely parents with children aged 2-6 years. As many as 31.4% of respondents have children aged 6 years, 40% of respondents have children aged 5 years, 8.6% of respondents have children aged 2 and 4 years. . These students are given a stimulus using a plasticine candle game. Stimulus is given by educators as well as parents at school and at home. Plasticine games help the child's fine motor development process develop optimally. Optimal fine motoric development of children determines children's writing skills.